Avoiding the interference of doxorubicin with MTT measurements on the MCF-7 breast cancer cell line - Luis, Carla (2019)
Doxorubicin (DOXO) is an adjuvant chemotherapy agent and is also commonly used in cell biology research. Cytotoxic assays in cell culture are frequently used in order to stablish drug concentrations that are useful for controlling cell proliferation. One common cytotoxic method used is 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT). Our present research aims to support future studies in engaging MTT assay using DOXO that exhibits a strong red coloration and fluorescence, and so it is assumed that DOXO may interfere with commonly used colorimetric assays such as MTT. The interference of DOXO in the MTT determination was evaluated in a Breast Cancer cell line Michigan Cancer Foundation-7 (MCF-7). The interference was evaluated by means of spectroscopic methods in particular spectrophometry and fluorescence spectroscopy of MTT and DOXO. We postulate that the medium and the MTT reagent itself can interfere on the metabolic activity method, so in order to achieve better results, DMEM was replaced by a neutral buffer like Phosphate-buffered saline (PBS). This protocol may be extremely useful in future studies involving DOXO.